Variations of Scale Height at F-Region Peak Based on Ionosonde Measurements during Solar Maximum over the Crest of Equatorial Ionization Anomaly Region - Yu-Jung Chuo (The Scientific World Journal)
Scale height is an important parameter in characterizing the shape of the ionosphere and its physical processes. In this study, we attempt to examine and discuss the variation of scale height, Hm, around the F-layer peak height during high solar activity at the northern crest of the equatorial ionization anomaly (EIA) region. Hm exhibits day-to-day variation and seasonal variation, with a greater average daily variation during daytime in summer. Furthermore, the diurnal variation of Hm exhibits an abnormal peak at presunrise during all the seasons, particularly in winter. This increase is also observed in the F2-layer peak height for the same duration with an upward movement associated with thermospheric wind toward the equator; this upward movement increases the N2/O ratio and Hm, but it causes a decrease in the F2-layer maximum critical frequency during the presunrise period.